2018
DOI: 10.3847/1538-4357/aac2ec
|View full text |Cite
|
Sign up to set email alerts
|

Infall Signatures in a Prestellar Core Embedded in the High-mass 70 μm Dark IRDC G331.372-00.116

Abstract: Using Galactic Plane surveys, we have selected a massive (1200 M ), cold (14 K) 3.6-70 µm dark IRDC G331. 372-00.116. This IRDC has the potential to form high-mass stars and, given the absence of current star formation signatures, it seems to represent the earliest stages of high-mass star formation. We have mapped the whole IRDC with the Atacama Large Millimeter/submillimeter Array (ALMA) at 1.1 and 1.3 mm in dust continuum and line emission. The dust continuum reveals 22 cores distributed across the IRDC. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 53 publications
7
94
0
Order By: Relevance
“…To reproduce it requires a more sophisticated modeling, which is beyond the scope of this work. From the derived values of the infall speed (1.6 km s −1 ), core radius (0.03 pc), molecular weight µ H 2 (2.8), and molecular hydrogen density (1.5×10 7 cm −3 ) we estimate a mass infall rateṀ (=4π R 2 n(H 2 )µ H 2 m H v in ) of 1.9×10 −2 M /yr, value similar to those reported in other high-mass star forming regions (eg., Garay et al 2002;Beuther et al 2002;Contreras et al 2018 The observed radial intensity profile of the massive core, shown in Figure 21, deviates significantly from a Gaussian profile but is well approximated with a Plummer-like radial intensity profile of the form,…”
Section: The Massive Core At the Center Of The Protostellar Clumpmentioning
confidence: 90%
See 1 more Smart Citation
“…To reproduce it requires a more sophisticated modeling, which is beyond the scope of this work. From the derived values of the infall speed (1.6 km s −1 ), core radius (0.03 pc), molecular weight µ H 2 (2.8), and molecular hydrogen density (1.5×10 7 cm −3 ) we estimate a mass infall rateṀ (=4π R 2 n(H 2 )µ H 2 m H v in ) of 1.9×10 −2 M /yr, value similar to those reported in other high-mass star forming regions (eg., Garay et al 2002;Beuther et al 2002;Contreras et al 2018 The observed radial intensity profile of the massive core, shown in Figure 21, deviates significantly from a Gaussian profile but is well approximated with a Plummer-like radial intensity profile of the form,…”
Section: The Massive Core At the Center Of The Protostellar Clumpmentioning
confidence: 90%
“…Our observations with spatial resolution of ∼0.03 pc, ten times smaller than that of Csengeri et al (2017), show that the number of cores per clump increases to 10, suggesting that we are resolving further fragmentation within MDCs. Recent studies of clumps with similar characteristics to those observed by Csengeri et al (2017) have reported levels of fragmentation ranging from 5 to 20 cores when observed at scales of 0.03-0.05 pc (eg., Lu et al 2018;Contreras et al 2018). Figure 19 shows the normalized cumulative distribution function (CDF), also known as empirical cumulative distribution function (eCDF).…”
Section: Mass Distributionmentioning
confidence: 99%
“…High-mass prestellar cores, defined here as cores with masses >30 M , are the cornerstone of the turbulent core accretion model (McKee & Tan 2003;Tan et al 2013Tan et al , 2014. However, they have not been unambiguously found in IRDCs (Zhang et al 2009Wang et al 2014;Ohashi et al 2016;Sanhueza et al 2017;Contreras et al 2018;Beuther et al 2018a;Kong et al 2018b). The case is different in more evolved high-mass star-forming regions.…”
Section: High-mass Star Formation Picturementioning
confidence: 99%
“…The early fragmentation in 70 µm dark-IRDCs results in a power law index slightly shallower than Salpeter. The most massive cores can accrete material, growing in mass quite quickly according to the recent finding of Contreras et al (2018). They determine an accretion rate of 2 × 10 −3 M yr −1 in a relatively massive prestellar core.…”
Section: Core Mass Functionmentioning
confidence: 99%
“…It can be explained, however, by the presence of at least one undetected heavily embedded (proto)star(s). For example, recent studies by Liu et al (2018b) using single-dish telescopes and Contreras et al (2018) using the Atacama Large Millimeter/submillimeter Array (ALMA) detected high accretion rates in massive quiescent cores, which are com- Table 3 for each of the three epochs (left to right). The images have been re-scaled by the relative calibration process described in Section 3.…”
Section: Variable Candidate Found In This Studymentioning
confidence: 99%